IMPLEMENTASI KEBIJAKAN KARTU IDENTITAS ANAK DI KELURAHAN TITI PAPAN, KECAMATAN MEDAN DELI - Sinaga, Dian Veronika; Hutahaean, Marlan; Tobing, Artha L (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
This research was conducted in Titi Papan Village, Medan Deli District, and this study aims to determine the performance of the implementation of the Child Identity Card Program. This study uses a descriptive qualitative approach with data collection techniques sourced from observations, interviews, and documents. The research informants who will provide information in this study are the village head as the key informant, the village employee in the field of government administration as the main informant, and the community who take care of the Child Identity Card as additional informants. The results of the study conducted through in-depth interviews with the village head, government administration employees, and the community, found that the implementation of the policy in making the Child Identity Card (KIA) has been running in accordance with the Regulation of the Minister of Home Affairs of the Republic of Indonesia Number 2 of 2016 concerning the Child Identity Card (KIA)